Business Cycle Fluctuations and Private Savings in OECD Countries: A Panel Data Analysis - Yvonne Adema; Lorenzo Pozzi (Tinbergen Institute, 2012)
We investigate the cyclicality of the private savings to GDP ratio for a panel of 19 OECD countries over the period 1971-2009. We find robust evidence that the private savings ratio is countercyclical. Three theories unambiguously predict a higher private savings ratio during recessions: a Ricardian offset effect, the presence of credit constraints, and precautionary savings. We find evidence only for the latter theory. Our estimations take into account a large number of econometric complications: persistence in the savings ratio, endogeneity of the regressors, cross-country parameter heterogeneity, cross-sectional dependence, stationarity issues, omitted variables, and instrument strength.
urn:NBN:nl:ui:15-1765/38219
Keywords: C23; E21; E32; 330; Private Savings; Business Cycles; Ricardian offset; Credit Constraints; Precautionary Savings; Dynamic Panel; Cross-Sectional Dependence; Sparen; Konjunktur; Liquiditätsbeschränkung; Panelforschung; OECD-Staaten